Star trek. Beyond [videorecording (DVD)] - Pine, Chris, 1980-; Quinto, Zachary; Urban, Karl, 1972-; Saldana, Zoë, 1978-; Cho, John, 1972-; Yelchin, Anton; Elba, Idris (Paramount Home Entertainment, 2016)
Dispatched on a rescue mission to the farthest reaches of space, the USS Enterprise is ambushed by Krall, a ruthless enemy sworn against the Federation. Crash-landing on an uncharted hostile world, Captain Kirk, Spock, and the crew are separated with no means of escape. Only Jaylah, a rebellious alien warrior, can help them reunite and find a way off the planet in a race against time to stop Krall's deadly army from triggering all-out galactic war.